Effectiveness of whole-body electromyostimulation on knee pain and physical function in knee osteoarthritis: a randomized controlled trial - Kast, Stephanie; Kemmler, Wolfgang; Roemer, Frank; Kohl, Matthias; Culvenor, Adam G.; Mobasheri, Ali; Uder, Michael; von Stengel, Simon (Scientific Reports, 2024)
In a randomized, controlled study, whole-body electromyostimulation (WB-EMS) was investigated as a promising alternative treatment technique compared to conventional strength training for the management of knee osteoarthritis (OA). Seventy-two overweight participants with symptomatic knee OA were randomly assigned to WB-EMS (n = 36) or a usual care group (UCG, n = 36). For seven months, the WB-EMS group received three times per fortnight a WB-EMS training, while the UCG was prescribed six-times physiotherapeutic treatments. We observed significant effects for the primary outcome “pain”, as determined by the Knee injury and Osteoarthritis Outcome Score (KOOS), with more favourable changes in the WB-EMS group vs UCG (between-group difference 9.0 points, 95%CI 2.9–15.1, p = 0.004). Secondary outcomes, including the other KOOS subscales (symptoms, function in daily living, function in sports/recreational activities and quality of life), 7 day pain diary, hip/leg extensor strength and lower limb function (30s sit-to-stand test), were also statistically significant in favour of the WB-EMS group. Overall, WB-EMS was found to be effective in relieving knee pain symptoms and improving physical function in individuals with symptomatic knee OA compared to usual care treatment. WB-EMS could be used as an alternative therapy in the management of knee OA; particularly for patients that cannot be motivated for conventional training.
CRIS-Team Scopus Importer:2024-09-13